Differences in kinematics and driver performance in elite female and male golfers - Parker, J.; Hellström, J.; Olsson, M. C. (Sports Biomechanics, 2022)
The aim of this study was to compare swing kinematic differences between women and men and investigate which variables predict clubhead speed (CHS) and carry distance (CD) whilst accounting for individual variation. Methods: Swing kinematics and driver performance data were collected on 20 (10 women) elite golfers (HCP 0.7 ± 1.4). We used Bayesian T-test for between sex comparison of swing kinematics and Bayesian Analysis of covariance (ANCOVA) to produce general linear models for CHS and carry distance for elite female and male golfers separately. Results: There was strong evidence that the driver performance variables CHS and CD were decreased in women compared to men, and two kinematic variables; time to arm peak speed downswing and angular wrist peak speed were slower in women. The ANCOVAs identified very strong to overwhelming evidence that participant as a fixed factor was a determinant of CHS for both women and men but was not a determinant of CD. Conclusion: when looking to enhance driver performance among high-level golfers, coaches should be aware that variables that determine CHS and CD differ among women and men and if the aim is to improve CHS coaches should not forget the importance of individual swing characteristics.